Single Phase Cascaded H-Bridge Inverter using Multi-Carrier PWM Technique for Grid power flow - S.Balamurugan, Chandla Ellis, M.J.Suganya, L.Annie Isabella (Mathematical Statistician and Engineering Applications, 2022)
Multilevel inverters typically have lower harmonic content in their output voltage and are utilised for high power and high voltage applications. Total harmonic distortion is greatly reduced by multilevel inverters with more levels. Using multicarrier PWM approaches, the output voltage’s harmonic content is decreased. MATLAB/SIMULINK is used to create a five-level cascaded multilevel inverter with a multi-carrier PWM approach. The output voltage’s total harmonic distortion is verified. Additionally, after adding grid integration requirements, the power flow from the inverter to the grid is certified and examined using LCL-Filter. By setting the reactive power to zero in MATLAB/SIMULINK, a Cascaded Multi-level inverter coupled to a single-phase grid is created to feed the grid.